CAN SOIL PENETRATION RESISTANCE AND BULK DENSITY BE DETERMINED IN A SINGLE UNDISTURBED SAMPLE? - Fernandes, Carolina [UNESP]; Silva, Roniram Pereira da [UNESP]; Marcelo, Adolfo Valente (Soc Brasileira De Ciencia Do Solo, 2015)
Soil quality indicators such as penetration resistance (PR) and bulk density (BD) are traditionally determined in a single undisturbed soil sample. The aim of this study was to assess the effect of PR measurements of undisturbed samples on the determination of BD in the same sample of two soils differing in clay contents. To this end, samples were collected from the 0.00-0.10 and 0.10-0.20 m layers of two soils of clayey and very clayey texture. Volumetric rings were used to collect a total of 120 undisturbed soil samples from each soil layer that were divided into two subsets containing 60 units each. One sample set, designated perforated samples, was used to determine PR and BD in the same undisturbed sample; the other, named intact samples, was used to determine BD only. Bulk density values for perforated and intact samples were compared by analysis of variance, using a completely randomized experimental design. Means were compared by the t-test at 5 %. The BD values for the clayey soil were similar in perforated and intact samples from the two layers. However, BD of the very clayey soil was lower in the perforated than in the intact samples at both depths. Therefore, PR and BD in clayey soils can be accurately determined in the same undisturbed sample whereas in very clayey soils, different samples are required for this purpose.
Keywords: soil physics; Latossolo Vermelho; clayey texture; very clayey texture